2013
DOI: 10.1016/j.pnpbp.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Putative neuroprotective agents in neuropsychiatric disorders

Abstract: In many individuals with major neuropsychiatric disorders including depression, bipolar disorder and schizophrenia, their disease characteristics are consistent with a neuroprogressive illness. This includes progressive structural brain changes, cognitive and functional decline, poorer treatment response and an increasing vulnerability to relapse with chronicity. The underlying molecular mechanisms of neuroprogression are thought to include neurotrophins and regulation of neurogenesis and apoptosis, neurotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 189 publications
1
74
0
6
Order By: Relevance
“…Potentially, suffering from both conditions may increase neuroprogressive pathways and lead to worsening treatment outcomes, relapse or treatment resistance. Adjunct interventions that may be considered include the addition of anti-inflammatory drugs such as COX-2 inhibitors (Muller and Schwarz, 2008) and the TNF antagonist, infliximab (Raison et al, 2013), medications with neuroprotective properties (e.g., antidepressants, mood stabilisers) (Dodd et al, 2013, Malhi et al, 2012, herbs and nutrients with anti-inflammatory and antioxidant properties (e.g., curcumin, resveratrol, omega-3 fatty acids, green tea, n-acetyl cysteine, CoQ10, selenium, zinc, alpha lipoic acid and vitamins such as A, C and E) (Alappat and Awad, 2010, Floyd, 1999, Kim et al, 2008, Lopresti et al, 2012, Scapagnini et al, 2012 and lifestyle changes known to enhance neurogenesis (e.g., sleep hygiene interventions, meditation, yoga, relaxation therapies and exercise) (Doraiswamy and Xiong, 2007, Kiecolt-Glaser et al, 2010, Lopresti et al, 2013.…”
Section: Do Obese and Overweight Psychiatric Populations Require Specmentioning
confidence: 99%
“…Potentially, suffering from both conditions may increase neuroprogressive pathways and lead to worsening treatment outcomes, relapse or treatment resistance. Adjunct interventions that may be considered include the addition of anti-inflammatory drugs such as COX-2 inhibitors (Muller and Schwarz, 2008) and the TNF antagonist, infliximab (Raison et al, 2013), medications with neuroprotective properties (e.g., antidepressants, mood stabilisers) (Dodd et al, 2013, Malhi et al, 2012, herbs and nutrients with anti-inflammatory and antioxidant properties (e.g., curcumin, resveratrol, omega-3 fatty acids, green tea, n-acetyl cysteine, CoQ10, selenium, zinc, alpha lipoic acid and vitamins such as A, C and E) (Alappat and Awad, 2010, Floyd, 1999, Kim et al, 2008, Lopresti et al, 2012, Scapagnini et al, 2012 and lifestyle changes known to enhance neurogenesis (e.g., sleep hygiene interventions, meditation, yoga, relaxation therapies and exercise) (Doraiswamy and Xiong, 2007, Kiecolt-Glaser et al, 2010, Lopresti et al, 2013.…”
Section: Do Obese and Overweight Psychiatric Populations Require Specmentioning
confidence: 99%
“…Recent literature has suggested that some of the benefits 477 exerted by aspirin could be mediated by GPR35 (Dodd et al, 2013). This is based in part on studies 478 designed to understand how aspirin application inhibits acute inflammation, irrespective of its effects 479 on the inhibition of prostaglandin synthesis.…”
Section: Fast Synaptic Transmission Is Mediated Synergistically By Mumentioning
confidence: 99%
“…Knowledge of the involvement of each of these pathways implies that specific agents that act on some or multiple of these pathways may thus block this cascade and have neuroprotective properties. 8) A recent study 9) has demonstrated that chronic treatment with celecoxib, a selective cyclooxygenase-2 (COX-2) inhibitor, resulted in a remarkable decrease in the frequency of spontaneous recurrent seizures (SRS) after pilocarpine-induced prolonged seizures.…”
Section: Design Synthesis and Potent Antiepileptic Activity With Lamentioning
confidence: 99%